Durability of Industrial Composites - Filho, Antonio Carvalho; Taylor and Francis (Boca Raton, FL : CRC Press, 2018)
Durability of Industrial Composites offers numerical and quantitative solutions to long-term composite failures that are useful to practicing engineers, researchers, and students. All modes of laminate long-term failure are contemplated, with resin toughness and environmental conditions considered. The book develops a simple unified equation to compute the load-dependent durability of laminates under the simultaneous action of cyclic and static loads. The load-independent durability and residual life of equipment immersed in corrosive chemicals are also discussed. The book presents a full discussion of the elusive strain-corrosion mode of failure as well as a complete solution to the durability issue of underground sanitation pipes. The currently accepted durability parameters of HDB, Sb and Sc are discarded as incorrect and replaced with the appropriate threshold parameters. The entirely new concept of the "anomalous failure" is fully discussed and solved. The effects of overpressure and spike strains, as well as of the operating temperature and moisture, are quantitatively evaluated and illustrated in numerical examples.
Part 1:-- Computation of Total Strains. Chapter 1. Ply Properties. Chapter 2. Laminate Circularity. Chapter 3. Computing the Total Ply Strains. Chapter 4. Laminate Matrices. Chapter 5. Total Strains in 55 Laminates. Chapter 6. Total Strains in 70 Laminates. Chapter 7. Total Strains in Hoop-Chop Sanitation Pipes. --Part 2:-- Computation of Durability. Chapter 8: the Eight Modes of Long-Term Failure. Chapter 9: The Regression Equations. Chapter 10: Temperature, Moisture and Resin Toughness. Chapter 11: Service Life and the Corrosion Barrier. Chapter 12: Long-Term Fiber Rupture. Chapter 13: Infiltration, Weep and Stiffness Failures. Chapter 14: Laminate Strain-Corrosion. Chapter 15: Abrasion Life. Chapter 16: The Unified Equation. Chapter 17: The Interaction Parameter Gsc. Chapter 18: Numerical Computation of the Interaction Parameter Gsc. Chapter 19: The Unified Equation Applied to API 15HR. Chapter 20: Short-Term Strengths of 55 Oil Pipes. Chapter 21: Impermeable Pipes. Appendix: The Fatigue Mechanism.
Includes bibliographical references and index.
Also available in print format.
Keywords: Composite materials -- Service life; Strength of materials; TECHNOLOGY & ENGINEERING / Material Science; composites corrosion; cyclic loading of composite materials; environment-dependent durability problems; load-dependent durability problems; materials fatigue; static loading of composite materials; Electronic books